49.3k views
4 votes
The solution to
15
a2 − 1
=
5
2a − 2
is

User Long Pham
by
5.6k points

2 Answers

4 votes

Answer: The solution is a=5

Step-by-step explanation: For this case the correct expression is:

15 / (a ^ 2 - 1) = 5 / (2a - 2)

Rewriting we have:

3 / (a ^ 2 - 1) = 1/2 (a - 1)

6 / (a ^ 2 - 1) = 1 / (a - 1)

6 (a - 1) = (a ^ 2 - 1)

6 (a - 1) = (a-1) (a + 1)

(a + 1) = 6

a = 6-1

a=5

User Luator
by
4.9k points
4 votes

Answer:

a = 1, 5

Explanation:

given,


(15)/(a^2-1)=(5)/(2a-2)


(3)/(a^2-1)=(1)/(2a-2)

3(2 a - 2) = a² -1

6 a - 6 = a² - 1

a² - 6 a + 5 = 0

a²- 5 a - a + 5 = 0

a( a - 5 ) -1 ( a - 5) = 0

( a - 1 )( a - 5 ) = 0

a = 1, 5

hence, on solving we get the value of a = 1,5

User Enrique Zetina
by
5.6k points